The Potency of Adenostemma platyphyllum as Antimelanogenic Agent: In-vitro and In-silico Studies - Lutfia Mutmainnah; Irmanida Batubara; Auliya Ilmiawati (Jurnal Kimia Sains dan Aplikasi, 2024)
Melanin is a crucial amino acid in determining human skin and hair pigmentation. Excessive melanin production can lead to hyperpigmentation and darkening of the skin. This study aims to assess the capability of Adenostemma platyphyllum as a tyrosinase enzyme inhibitor. It predicts its anti-melanogenic activity through molecular docking with proteins involved in the melanogenesis process. The in-vitro approach was conducted by determining the tyrosinase enzyme inhibition capacity, while the in-silico approach involved ligand binding to target proteins from melanogenesis pathways. The highest tyrosinase inhibition capacity was observed in the ethanol extract, with values of 9.74 Kojic Acid Equivalent (KAE)/g extract (L-tyrosine) and 17.91 (KAE)/g extract (L-DOPA). Molecular docking analysis showed that the binding of eriodictyol 7-O-sophoroside (ΔG = -9.7 kcal/mol) has the best energy affinity for the PKC-β protein, genistein (ΔG = -7.5 kcal/mol) for the tyrosinase-related protein-1 (TYRP1) protein, eriodictyol 7-O-sophoroside (ΔG = -10.2 kcal/mol) for the cGMP protein, vincosamide (ΔG = -7.2 kcal/mol) for the microphthalmia-associated transcription factor (MITF) protein, and dicaffeoylquinic acid (ΔG = -7.4 kcal/mol) for the β-catenin protein. Based on a comparison of in-vitro and in-silico studies, melanogenesis inhibition is more potent in the PKC-β and cGMP pathways than direct tyrosinase inhibition because they exhibit lower binding energy.